THE INFLUENCE OF EXPERIENTIAL MARKETING, STORE ATMOSPHERE, AND LOCATION ON REPURCHASE INTENTION AT SARUNECOFFEE AND EATERY IN KARO REGENCY - Kezia Karina Perangin Angin; Alfifto; Wan Rizca Amelia; Indawati Lestari; Fitriani Tobing (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of experiential marketing, store atmosphere and location on repurchase interest at Sarune Coffee and Eatery in Karo Regency. This study uses a descriptive research type with a quantitative approach, which uses a multiple linear regression method with the SPSS 23 program. Data collection through the distribution of questionnaires. The population of this study is everyone who has been a consumer at Sarune Coffee and Eatery in Karo Regency with a sample of 99 respondents. The sampling technique uses Nonprobability Sampling, with a purposive sampling method. Data analysis techniques are carried out using instrument tests, classical assumption tests, statistical tests and hypothesis tests. Based on the research results, it shows that (1) Experiential Marketing has a positive and significant effect on repurchase interest at Sarune Coffee and Eatery in Karo Regency, (2) Store Atmosphere has a positive and significant effect on repurchase interest at Sarune Coffee and Eatery in Karo Regency, (3) Location has a positive and significant effect on repurchase interest at Sarune Coffee and Eatery in Karo Regency, and (4) Experiential Marketing, Store Atmosphere and Location simultaneously have a positive and significant effect on repurchase interest at Sarune Coffee and Eatery in Karo Regency.